Servant leadership, caring ethical climate, organizational citizenship behaviour, and intention to leave among employees in retail industry - Wong, Hin Chow (2020)
The purpose of this study is to investigate the potential influence of servant leadership on the intention of high performing workers in Malaysia in the retail industry to leave their work. Existing literatures indicate that there is a lack of research on the effect of leadership style on the intention to leave among high performers in this industry. Servant leadership is proposed as a direct predictor of high performers’ intention to leave while organizational citizenship behaviour is proposed as a mediator of this relationship. The possible moderating effect of caring ethical climate on the relationship between servant leadership and organizational citizenship behaviour is also examined. Purposive non-probability sampling is used to collect the data in this study. Data from 131 high performing employees from the Malaysian retail industry were collected. Multivariate analysis with Partial Least Square Structural Equation Modeling (PLS-SEM) found support for four hypotheses including the support for organizational citizenship behaviour as a mediator for the relationship between servant leadership and high performers’ intention to leave. But there was no evidence to indicate that caring ethical climate moderated the relationship between servant leadership and organizational citizenship behaviour. From a practical standpoint, this study provides additional knowledge in the area of employee turnover which will enable HR practitioners to have a better understanding on how to reduce the intention to leave among high performers in the retail industry and ultimately reduce the rate of turnover among this group of employees in this industry. Whilst at the same time, this study also contributes to the existing number of valuable researches that provide the much-needed knowledge in understanding the employee turnover phenomenon.